Using geophysical surveys to test tracer‐based storage estimates in headwater catchments. Issue 23 (15th June 2016) - Soulsby, C.; Bradford, J.; Dick, J.; McNamara, J. P.; Geris, J.; Lessels, J.; Blumstock, M.; Tetzlaff, D.
Abstract: Hydrogeophysical surveys were carried out in a 3.2 km 2 Scottish catchment where previous isotope studies inferred significant groundwater storage that makes important contributions to streamflow. We used electrical resistivity tomography (ERT) to characterize the architecture of glacial drifts and make an approximation of catchment‐scale storage. Four ERT lines (360–535 m in length) revealed extensive 5–10 m deep drift cover on steeper slopes, which extends up to 20–40 m in valley bottom areas. Assuming low clay fractions, we interpret variable resistivity as correlating with variations in porosity and water content. Using Archie's Law as a first approximation, we compute likely bounds for storage along the ERT transects. Areas of highest groundwater storage occur in valley bottom peat soils (up to 4 m deep) and underlying drift where up to 10 000 mm of precipitation equivalent may be stored. This is consistent with groundwater levels which indicate saturation to within 0.2 m of the surface. However, significant slow groundwater flow paths occur in the shallower drifts on steeper hillslopes, where point storage varies between ~1000 mm–5000 mm. These fluxes maintain saturated conditions in the valley bottom and are recharged from drift‐free areas on the catchment interfluves. The surveys indicate that catchment scale storage is >2000 mm which is consistent with tracer‐based estimates. Copyright © 2016 John Wiley & Sons, Ltd.